THE INTEGRATIVE LEARNING MODEL TYPE WEBBED IN SPEAKING AT CLASS V STUDENTS OF SD NEGERI CITAMAN 1 - Aminah, Aminah (Teaching English as a Foreign Language Overseas Journal, 2022)
The aim of this research is to identify the effectiveness of the Webbed type Integrative Learning Model in speaking for class V students at SD Negeri Citaman 1. The researcher was applied pre-experimental design the population is the seven grade students of SD Negeri Citaman 1 in academic year 2021/2022. In analyzing the numerical data, the writer was used SPSS for windows.  Researchers can conclude based on the research results that the integrated learning model assisted by technology media can improve the quality of student learning according to the objectives of integrated learning effectively and efficiently by using the Webbed type, especially in speaking. Both in terms of arranging material, presenting, and coaching students during the teaching and learning process, a teacher continues to play an active integrated role with the help of technological media and can improve the quality of student learning according to the objectives of integrated learning effectively and efficiently by using the Webbed type. Both in terms of preparing material, presenting and coaching students during the teaching and learning process